PEMBINAAN EKSTRAKURIKULER BOLABASKET SISWA SMP NEGERI 1 MANDAU - Mimi Salyeni Salim; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, SMP Negeri 1 Mandau is one of the schools that implement extracurricular activities basketball. However, the implementation of this extracurricular less walk sebagimana that diharpkan. It is caused by many factors, including, motivation of students, teachers, counselors or coaches, and facilities. This research is a descriptive that aims to reveal about the picture Extracurricular Execution Basketball in SMP Negeri 1 Mandau. The study population was 45 people. Sampling was done by total sampling technique, so the sample amounted to 45 people. Instruments used to collect data was questionnaire or questionnaires using Likert scale. Data were analyzed using frequency distribution formula in the form of a percentage. From the data analysis obtained the following results: variable as a mentor teacher, the average yield scores obtained 64.1% of the respondents' statements, where the score is at the level of good, because it is located on the questionnaire class group is 61-80. And the selection of athletes / students, the average yield scores obtained 55.9% of the respondents' statements, because it lies in the questionnaire class group 41-60. In general it can be concluded that the extracurricular coaching basketball at SMP Negeri 1 Mandau is enough going well, although there are still shortcomings which should be improved for the sake of achievement basketball SMP Negeri 1 Mandau in the future.Keywords : Extracurricular coaching Basketball